Evaluation of Development Program at Persinas Asad Pencak Silat Education, Palembang City - Herwansyah, Herwansyah; Kristina, Putri Cicilia; Akhbar, M Taheri (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study is to obtain a comprehensive picture of the implementation process of the pencak silat sports training program at Persinas Asad pencak silat college. This research is an evaluation of the Persinas Asad pencak silat achievement development program in Palembang city using a qualitative research method, using the CIPP program evaluation approach model, the data sources for this research are PERSINAS ASAD administrators, coaches, athletes, parents of athletes and administrators of City IPSI Palembang. data collection techniques are observation, in-depth interviews, documentation and data triangulation. The obtained data were analyzed by data reduction, data presentation and inference. The results of the study show that it is good from a contextual point of view, while the input, process and product of this training program are not yet viable to continue because they have failed to mold the pencak silat athletes into outstanding athletes at the industry, regional or national level. However, a change is needed in further improvements in terms of facilities and infrastructure as well as funding so that implementation can be scaled up in the future. This program can be continued with various suggestions and inputs to the training program related to science and technology in sports. The conclusion of the research is that the context aspect is good, while the input, process and product of this coaching program are not yet feasible.